2022
DOI: 10.1182/bloodadvances.2022007741
|View full text |Cite
|
Sign up to set email alerts
|

HLA-matching with PTCy: a reanalysis of a CIBMTR dataset with propensity score matching and donor age

Abstract: Blood or marrow transplantation (BMT) outcomes using haploidentical donors (Haplo) and post-transplant cyclophosphamide (PTCy)-based graft versus host disease (GVHD) prophylaxis compare favorably to using HLA-matched donors with calcineurin inhibitor-based GVHD prophylaxis. A recent CIBMTR analysis of patients receiving homogenous PTCy-based prophylaxis found that, with reduced intensity conditioning, Haplo BMTs had worse outcomes than matched unrelated donor (MUD) BMTs. Due to significant differences in chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…In the current era, the use of haploidentical donors in the broad scope of BMT has evolved signi cantly since the advent of posttransplantation cyclophosphamide (PTCy). [7][8][9][10] The role of haploidentical donors in MDS/MPN offers the potential advantage of available donors in a timely manner for an otherwise incurable malignancy. Additionally, nding a fully matched donor in the donor registry can be challenging for non-White patients due to the lower diversity of donors from these populations.…”
Section: Introductionmentioning
confidence: 99%
“…In the current era, the use of haploidentical donors in the broad scope of BMT has evolved signi cantly since the advent of posttransplantation cyclophosphamide (PTCy). [7][8][9][10] The role of haploidentical donors in MDS/MPN offers the potential advantage of available donors in a timely manner for an otherwise incurable malignancy. Additionally, nding a fully matched donor in the donor registry can be challenging for non-White patients due to the lower diversity of donors from these populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent single-center and registrybased studies that assessed transplantation outcomes as per disease risk, demonstrated that Haplo-HSCT with PTCy outcomes including RI appeared comparable to those of HLA-matched transplants with No PTCy. 24,25,39 Yet the scenario may differ in the setting of UD-HSCT, which emphasizes the importance of our finding of a 2-year RI of 24.9% with PTCy-based anti-GVHD prophylaxis in AML patients undergoing UD-HSCT. The RI we observed in the PTCy cohort is very similar to the figures of 11%-39.1% observed in the previous studies that evaluated outcomes of UD-HSCT with PTCy including previous studies from our group.…”
Section: Discussionmentioning
confidence: 75%
“…[17][18][19] From a clinical point of view, GVHD (especially in its chronic form) correlates with RI and besides the actual occurrence of clinical relapse, it is almost the only read-out assay for the so-called GVL effect. 5,6,8,38,39 As PTCy anti-GVHD prophylaxis resulted in a significant reduction of GVHD and even more so of cGVHD, 14,15,24 there is further theoretic support to the notion that PTCy is attributed to the high RI observed post-Haplo-HCST with its administration. However, subsequent single-center and registrybased studies that assessed transplantation outcomes as per disease risk, demonstrated that Haplo-HSCT with PTCy outcomes including RI appeared comparable to those of HLA-matched transplants with No PTCy.…”
Section: Discussionmentioning
confidence: 96%
“…It has allowed, because of its effectiveness and relative simplicity, the widespread use of this procedure worldwide. Two randomized trials have shown superiority of haplo-HSCT over UCBT [13,14], while most retrospective studies have shown similar outcomes compared with MUD and MSD transplants [15][16][17][18].…”
Section: Donor Availabilitymentioning
confidence: 99%